PENGARUH PERSONAL TRAITS PEGAWAI TERHADAP KEPUASAN KERJA WORK FROM HOME (WFH) SAAT PANDEMI COVID-19 - Yuniasih Tinekaningrum; Kunto Adi Wibowo; Henny Sri Mulyani (Jurnal Sosioteknologi, 2021)
Social Distancing has been imposed almost in all countries affected by Covid-19 including Indonesia, causing almost all companies to urge their employees to work from home (WFH). Teleworking in pandemic conditions is not a person’s choice, but a compulsion. This research is aimed at finding the relationship between personal traits and job satisfaction towards WFH. This study employed the big five personality and demography variables such as sex, age, ranks, and duration of work as control variables. This research uses a quantitative method, through a survey of 129 administration staff (Tendik) at the Institut Teknologi Bandung (Bandung Institute of Technology). The results of this study have demonstrated that there is a positive influence from the personal traits toward job satisfaction in WFH. Another finding is there is a negative influence from the rank of workers toward their job satisfaction in WFH setting, while other demography variables such as sex, age, and work duration have not significantly predicted job satisfaction towards WFH. Technological and cultural aspects of workspace communication are further discussed as a contributing factor that is not directly measured in this research.